HUBUNGAN PANJANG BERAT DAN POLA PERTUMBUHAN BIVALVE (POLYMESODA EROSA) DI KAMPUNG MAKIMI, KABUPATEN NABIRE, PROVINSI PAPUA TENGAH - Frits Aripatra Maitindom; Hendri S. Lakatompessy (Yayasan Nusantara Hasana Berdikari, 2023)
Utilization of bivalves by people living on the coast of Nabire Regency as a source of livelihood with economic value. There is a dependency of coastal communities on marine biota components, especially bivalves, so this research was carried out with the focus of the objective being to determine the length and weight of the bivalves caught, the relationship between the length and weight of the bivalves, and the growth patterns of the bivalves. This research was carried out from 20 to 30 April 2023 in Makimi Village, Makimi District, Nabire Regency, Central Papua Province. The number of samples was 150 specimens obtained from sampling results on 9 transects in the mangrove forest of Makimi Village, Makimi District, Nabire Regency. Analysis of the relationship between shell length and weight can be used to study growth patterns. The length of the shell in bivalves is used to explain their growth, while weight can be considered as a function of this length. The relationship between bivalve shell length and weight almost follows the cubic law, namely that the weight of a bivalve is the cube of its length. Based on research results, Polymesoda erosa shells have varying sizes, namely the smallest size is 41.1 mm to the largest size is 79.3 mm. with the largest length frequency distribution being in the 56.1 – 60.1 mm length class with 36 specimens and the smallest length frequency distribution being in the 76.1 – 80.1 mm class with 2 specimens. The average weight of Polymesoda erosa individuals is 70.5 g. The largest individual weight frequency distribution of Polymesoda erosa was in the 47.0 – 66.9 g class range for 49 specimens and the smallest weight distribution was in the 167.0 – 186.9 g class range for 2 specimens. The relationship between individual body length and body weight of Polymesoda erosa bivalves/shellfish as a whole results in a regression equation, namely W = 0.0009L2.7573, intercept (a) = 0.0009 and slope which is expressed as a regression coefficient (b) = 2.7573.